Studying on the design and simulation of collision protection system between vehicle and pedestrian. (January 2020) - Lu, Yujun; Shen, Jiafeng; Wang, Chunqing; Lu, Honghao; Xin, Jiancheng
Pedestrian protection technology has become the most important issue in the field of vehicle safety. The design and simulation method of pedestrian protection system for vehicles is studied based on the Teoriya Resheniya Izobreatatelskih Zadatch theory in this article. The optimal solution of a new type of all-around airbag system mounted to the front of vehicles is presented after performing some Teoriya Resheniya Izobreatatelskih Zadatch analysis tools, such as the component analysis, causal analysis, resource analysis, and contradiction analysis. The digital modeling is carried out on the airbag deployments by SolidWorks, and the simulation analysis is performed on the collision between vehicle and pedestrian head by HyperWorks and LS-DYNA. The results show that the vehicle equipped with the front-end all-around airbag than without can play a better role in pedestrian head protection during the collision, making the maximum value of head injury criterion decrease by 66.7%, effectively reducing the collision damage and verifying the feasibility of the solution.